2019
DOI: 10.1016/j.bbmt.2019.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib Therapy Is Associated with Improved Outcomes for FMS-like Tyrosine Kinase 3 Internal Tandem Duplication Acute Myeloid Leukemia Relapsing after Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: The optimal therapy for patients with acute myeloid leukemia (AML) with FMS-like tyrosine kinase 3 internal tandem duplication (FLT3-ITD) who relapse after allogeneic hematopoietic stem cell transplantation (allo-HSCT) remains unclear. In this study we retrospectively evaluated the efficacy of sorafenib combined with other therapeutic strategies as salvage therapy for these patients. Eighty-three AML patients with FLT3-ITD relapsing after allo-HSCT were enrolled in this study. Fifty-three patients received sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Of note, many patients with R/R FLT3-ITD AML in QuAN-TUM-R and other studies mentioned above [10,16,28,30] did not receive FLT3 inhibitor therapy as a first-line therapy, which mD 3 1 7 X Xight not reflect the current population of patients who may be undergoing receiving an allo-HSCT as a part of consolidation after initial therapy with an FLT3 inhibitor [8]. Preclinical data show that quizartinib has antitumor activity in FLT3-ITD-D 3 1 8 X Xmutated AML models that are resistant to the FLT3 inhibitor midostaurin, potentially due to a more complete and sustained inhibition of the FLT3 signaling pathway [34].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Of note, many patients with R/R FLT3-ITD AML in QuAN-TUM-R and other studies mentioned above [10,16,28,30] did not receive FLT3 inhibitor therapy as a first-line therapy, which mD 3 1 7 X Xight not reflect the current population of patients who may be undergoing receiving an allo-HSCT as a part of consolidation after initial therapy with an FLT3 inhibitor [8]. Preclinical data show that quizartinib has antitumor activity in FLT3-ITD-D 3 1 8 X Xmutated AML models that are resistant to the FLT3 inhibitor midostaurin, potentially due to a more complete and sustained inhibition of the FLT3 signaling pathway [34].…”
Section: Discussionmentioning
confidence: 70%
“…In a landmark analysis from day 60 after HSCT, the median OS was 16.2 months in patients who continued gilteritinib after allo-HSCT versus 8.4 months in those who did not [28]. Several retrospective and observational analyses have also demonstrated that treatment with FLT3 inhibitors is associated with improved outcomes in patients with FLT3-ITD AML who have relapsed after HSCT [10,29,30]. Preclinical data and a recent case study suggest that treatment with FLT3 inhibitors after allo-HSCT could enhance graft-versus-leukemia effects in addition to having direct effects on FLT3 mutation-positive leukemia cells [31,32], lending further support for their potential use in this setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting mutant FLT3 by small molecule inhibitors has rapidly emerged as a new therapeutic approach in patients with AML. Different FLT3 inhibitor therapeutic agents have been developed and are summarized in Tables 1, 2 [9,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Flt3mentioning
confidence: 99%
“…( 30 ) and Xuan et al. ( 31 ) also revealed enhanced OS comparing sorafenib with salvage chemotherapy in FLT3 (+) rrAML, which should be further confirmed in RCT. Finally, midostaurin might be specifically effective in the untreated AML rather than rrAML, since in vitro studies, midostaurin had broader activity and might achieve greater clinical utility in newly diagnosed AML with blasts tending to be less addicted to FLT3 -mediated signaling than rrAML ( 32 ).…”
Section: Discussionmentioning
confidence: 71%